PARADIGMA PENELITIAN KUALITATIF DALAM RISET AKUNTANSI: DARI IMAN MENUJU PRAKTIK - Ari Kamayanti (InFestasi, 2015)
This article aims to explain that a qualitative method is not just a technique. More than that, it is a manifestation of belief or assumption of god, reality, self and sciene. Through linkages between assumptions, variousn research paradigm can be mapped. Qualitative research of course have difference assumption compared to quantitative approach. It should be realized by the researchers, tht the research method chosen was part of her/his responsibility as a human being in the building of civilization. Key words: research, civilization, assupmtion, paradigm, qualitative